The effect of dialysates and ultrafiltrates of plasma of saline-loaded dogs on toad bladder sodium transport - Buckalew, Vardaman M. (1970)
In order to obtain direct evidence for the existence of a natriuretic hormone, dialysates and ultrafiltrates of plasma of dogs expanded with saline were tested for effects on sodium transport by the toad urinary bladder. Dialysate was obtained by dialysis of blood in vivo in a clinical dialyzer and by dialysis in vitro of small volumes of blood using a miniature model of the clinical dialyzer. Ultrafiltrates were prepared using selective molecular filters which permit passage of substances on the basis of molecular weight and three dimensional configuration. Dialysates and ultrafiltrates of hydropenic dogs caused a change in toad bladder potential difference of + 1% and in short circuit current of - 5%. In contrast, dialysates and ultrafiltrates from expanded dogs caused a change in potential difference of - 23% and in short circuit current of - 32%, a highly significant difference. Onset of reduction of short circuit current occurred within 3-5 min, reaching a maximum in 10-20 min. The effect was rapidly reversible, was specific for the serosal surface of the bladder, and could not be explained on the basis of nonspecific alterations in ionic composition or by dilutional effects. Ultrafiltrates of jugular vein plasma caused significantly more reduction of short circuit current than ultrafiltrates of femoral vein plasma. The data indicate the presence in plasma of saline-loaded dogs of a dialyzable inhibitor of toad bladder sodium transport. Ultrafiltrate studies using membranes of appropriate selectivity suggest the factor has a molecular weight of less than 3000.